2015
DOI: 10.4196/kjpp.2015.19.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Inhibits Morphological Changes in LPS-Stimulated Macrophages by Blocking NF-κB Pathway

Abstract: The present study showed that silymarin, a polyphenolic flavonoid isolated from milk thistle (Silybum marianum), inhibited lipopolysaccharide (LPS)-induced morphological changes in the mouse RAW264.7 macrophage cell line. We also showed that silymarin inhibited the nuclear translocation and transactivation activities of nuclear factor-kappa B (NF-κB), which is important for macrophage activation-associated changes in cell morphology and gene expression of inflammatory cytokines. BAY-11-7085, an NF-κB inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 44 publications
2
31
0
1
Order By: Relevance
“…After LPS prestimulation, we showed that a large proportion of cells change their morphology. As observed by Kim et al [ 37 ], these changes could be related to rearrangements of actin filaments as a response to inflammatory stimuli (e.g., the formation of lamellipodia and filopodia). Such a mechanism is required for cell adhesion and migration to the sites of inflammation.…”
Section: Discussionmentioning
confidence: 78%
“…After LPS prestimulation, we showed that a large proportion of cells change their morphology. As observed by Kim et al [ 37 ], these changes could be related to rearrangements of actin filaments as a response to inflammatory stimuli (e.g., the formation of lamellipodia and filopodia). Such a mechanism is required for cell adhesion and migration to the sites of inflammation.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies showed that LPS stimulation caused significant pathophysiological alterations of RAW264.7 macrophages, which is related to participation of macrophages in the inflammatory processes upon pathogen stimulation at nano‐scale along with secretion of inflammatory mediators (Pi et al ., ; Kim et al ., ). Nitric oxide (NO), which is one of important inflammatory mediators, plays an key role in numerous pathophysiological conditions, including inflammation and infection (Förstermann and Sessa, ), and then we determined whether DMY could inhibit NO secretion.…”
Section: Resultsmentioning
confidence: 97%
“…4A , CA treatment significantly inhibited APAP-induced TNF-α, IL-1β, IL-6 and MCP-1 mRNA expression. NF-κB plays essential roles in transcriptional induction of those genes involved in inflammation [ 20 ]. Here, we assessed the effects of CA on NF-κB signaling pathway.…”
Section: Resultsmentioning
confidence: 99%